South African university students' user experience of mobile applications for anxiety and depression - Chipps, Wesley (Department of Psychology, 2025)
Background: Globally, university students have been shown to be disproportionately affected by common mental disorders (CMDs). The primary CMDs reported by students have been anxiety and depression. Research on South African students has proven no exception. Moreover, this predicament is worsened by low rates of help-seeking, historically entrenched systemic inequality regarding access to resources, a lack of culturally appropriate interventions, and a population that tends to be overly self-reliant. Objective: With the prevalence of CMDs in mind, as well as the many challenges students face, it was deemed worth exploring current, available alternatives. Given some evidence for the use of mobile mental health (MMH) applications (apps) among university students in high income countries, the current study aimed to investigate South African university students' user experience of MMH apps for depression and anxiety. Methods: South African students in the psychology department of the University of Cape Town were recruited to make use of two MMH apps, Headspace and Woebot, for two weeks total, but one week per app. They then completed online questionnaires related to their experience of using these apps, and semi-structured interviews were conducted, recorded, and transcribed by the researcher. Due to a lack of meaningful data from the online questionnaires, only the semi-structured interviews were used for analysis. Braun and Clarke's (2006) method of thematic analysis was used to analyse the data. Results: After analysing the semi-structured individual interviews, themes were defined, described, and discussed. The participants expressed that the apps facilitated insight and self-awareness, and were found to be supportive, encouraging, and convenient. However, they valued different aspects of the two apps, with each offering something that the other did not. The importance of each design was also highlighted as a vital factor in the overall user experience, while affordability was also emphasised for the student population in particular. Conclusion: The two apps were found to be accessible and acceptable for participants in this South African university setting. Additionally, user experience design enhanced their experiences. However, as each app offered different approaches and benefits, the integration of features could be something to work towards. There are also important ethical considerations that need to be factored before recommending them. Further research and development are required in order to address these concerns.